2022
DOI: 10.1111/jre.13014
|View full text |Cite
|
Sign up to set email alerts
|

MZB1 targeted by miR‐185‐5p inhibits the migration of human periodontal ligament cells through NF‐κB signaling and promotes alveolar bone loss

Abstract: Objective To explore the role of Marginal Zone B and B‐1 Cell‐Specific Protein (MZB1), a novel molecule associated with periodontitis, in migration of human periodontal ligament cells (hPDLCs) and alveolar bone orchestration. Background MZB1 is an ER‐localized protein and its upregulation has been found to be associated with a variety of human diseases. However, few studies have investigated the effect and mechanism of MZB1 on hPDLCs in periodontitis. Methods Gene expression profiles in human gingival tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…Based on the prediction of circRNA-miRNA, we selected three circRNAs as potential fundamental molecules in the circRNA-miRNA-mRNA network.it is reported that the miR-185-5p inhibits mRNA expression levels of Runx2 in hPDLCs (Li et al 2022). This nding was accordant with the circRNA-miRNA-mRNA network(Fig.…”
Section: Qrt-pcr Validation Of Differentially Expressed Circrnasmentioning
confidence: 54%
“…Based on the prediction of circRNA-miRNA, we selected three circRNAs as potential fundamental molecules in the circRNA-miRNA-mRNA network.it is reported that the miR-185-5p inhibits mRNA expression levels of Runx2 in hPDLCs (Li et al 2022). This nding was accordant with the circRNA-miRNA-mRNA network(Fig.…”
Section: Qrt-pcr Validation Of Differentially Expressed Circrnasmentioning
confidence: 54%
“…This result is consistent with the previous studies that have demonstrated the upregulation of MZB1 in patients with aggressive periodontitis and chronic periodontitis. 2,3,8,[21][22][23] The MZB1 gene (marginal zone B-and B1-cell-specific protein) encodes for the protein MZB1 and is defined in the human gene database 24 as a gene that interacts with both heavy and light chains of IgM (immunoglobulin M) to facilitate its assembly and secretion. The pathways related to the MZB1 gene encompass positive regulation of the biosynthesis process of immunoglobulin, apoptosis, cell proliferation, B-cell proliferation regulation, and integrin activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few studies have examined the effect of MZB1 on human periodontal ligament cells (hPDLCs) in the presence of periodontitis and the mechanisms underlying this effect. Li et al performed experiments to determine the role of hPDLCs in migration and alveolar bone organization [ 148 ]. Bioinformatics analysis revealed that MZB1 is one of the most significantly upregulated genes in patients with periodontitis.…”
Section: New Findings From Clinical and Basic Research On The Alveola...mentioning
confidence: 99%
“…Bioinformatics analysis revealed that MZB1 is one of the most significantly upregulated genes in patients with periodontitis. mZB1, as a target gene of miR-185-5p, plays an important role in suppressing hPDLC migration through the NF-κB signaling pathway and exacerbating alveolar bone loss [ 148 ]. Bioinformatics analysis was used in this study [ 148 ].…”
Section: New Findings From Clinical and Basic Research On The Alveola...mentioning
confidence: 99%
See 1 more Smart Citation